Hydrothermal Synthesis and Crystal Structure of a Nickel(II) Coordination Polymer Assembled by 5-(3’-Carboxylphenyl)nicotinic Acid - Hua, Xiaoying (Asian Journal of Chemistry, 2012)
A novel nickel(II) coordination polymer with 5-(3'-carboxylphenyl)nicotinic acid [L=5-(3'- carboxylphenyl)nicotinic acid] has been prepared by hydrothermal synthesis and characterized by single-crystal X-ray diffraction X-ray diffraction analysis reveals that the ligand (L) adopt chelating bidentate and monodentate modes. The L ligands bridge Ni(II) ions to give rise to a two-dimensional structure.